Cost-Effectiveness of Conbercept vs. Ranibizumab for Age-Related Macular Degeneration, Diabetic Macular Edema, and Pathological Myopia: Population-Based Cohort Study and Markov Model - Cui, Zhuang; Zhou, Wei; Chang, Qinxue; Zhang, Tiantian; Wang, Hui; Meng, Xiangda; Liu, Yuanyuan; Yan, Hua (Frontiers in Medicine, 2021)
Background: With the advent of China’s aging society, fundus diseases related to pathological neovascularization, including age-related macular degeneration (AMD), diabetic macular edema (DME) and pathological myopia (PM), have become an increasingly serious medical and health problem. As effective drugs of the treatment, conbercept and ranibizumab have been commonly used and covered by the national basic medical insurance in China. However, the pharmacoeconomic evaluation of conbercept versus ranibizumab for DME and PM remains lacking. Our study would assess the cost-effectiveness of conbercept and ranibizumab for the treatment of AMD, DME and PM from the perspective of Chinese payers. Methods: A Markov chain model was constructed based on patient visual conditions indicated by the number of letters in best corrected visual acuity (BCVA). We conducted models based on real-world scenario to calculate the cost per quality adjusted life-year (QALY) gained. One year cycle length and a 10-year simulation treatment were applied, and the number of injections of conbercept and ranibizumab was assumed to the average number within ten years. Transition probabilities, costs, utility data and other parameters were obtained from literature searches. A 3.5% discounting rate was applied for both the costs and utilities. Results: The incremental cost-effectiveness ratios (ICERs) were more favorable for conbercept than ranibizumab in the treatment of AMD, DME and PM, with associated ICER of 66669 RMB, -258813 RMB and -373185 RMB per QALY gained. Compared with ranibizumab, the incremental effectiveness of conbercept in the treatment of AMD, DME and PM was -0.665 QALYs, 0.215 QALYs and 0.029 QALYs, respectively. The sensitivity analysis showed the same findings, although the ICER is sensitive to the costs of this program. Conclusions: Under the current Chinese healthcare setting, conbercept is suitable and cost-effective in the treatment of AMD, DME and PM compared with ranibizumab.